Outcome of Primigravida with high foetal head at term or onset of labour (Journal of Dhaka Medical College, 2018)
Objective: To determine the causes of high foetal head and their relative frequencies in primigravidae presenting at term and to determine the proportion of these patients undergoing lower segment caesarean section or vaginal delivery. Design: A descriptive study.Place and duration of study: The study was carried out at Mugda Medical College Hospital from March 2017 to June 2017.Materials and Methods: A total of 50 primigravidae patients presenting at term and having a single pregnancy were randomly selected. On the basis of history, Physical examination and abdominal ultrasonography, patients having a high foetal head were recognized and their causes documented.Results: Out of 50 primigravidae, with high foetal head there was foetal malpresentation 17(34%), Cephalopelvic disproportion 13(26%) , Foetal distress 12(24%). Lower segment caesarian section was the management of choice in more than half of the patients with high foetal head.Conclusions: Foetal malpresentation & Cephalopelvic disproportion were the major cause of high foetal head in this study and lower segment Caesarean section was the mode of delivery in more than half of the patients with high foetal head.J Dhaka Medical College, Vol. 26, No.2, October, 2017, Page 122-125